2020
DOI: 10.31557/apjcp.2020.21.2.563
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Triple Negative Breast Cancer: Correlation between Androgen Receptor Expression and Pathological Response

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous disease on the pathological, molecular, and clinical levels. It represents approximately 17% of all breast cancers (BCs) and have aggressive behavior compared to other molecular subtypes. QNBC is TNBC that lacks the expression of androgen receptor (AR), Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER-2) and accounts for 63%-87% of TNBC with more aggressive behavior than the other molecular subtypes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Hence, knowledge about differences between TNBCs in the young and the elderly could lighten the differences in therapeutic approach, as older patients could be less responsive to conventional chemotherapy and might benefit more from a more personalized therapeutic approach (e.g., anti-androgen therapy) [ 33 ]. Even though AR-positive tumors appeared more often in postmenopausal patients [ 26 , 34 , 35 ] and a higher percentage of postmenopausal women was found in the LAR subtype [ 36 ], there was no significant correlation between AR and menopausal status found [ 31 , 37 , 38 ].…”
Section: Clinical Characteristics Of Ar-positive Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, knowledge about differences between TNBCs in the young and the elderly could lighten the differences in therapeutic approach, as older patients could be less responsive to conventional chemotherapy and might benefit more from a more personalized therapeutic approach (e.g., anti-androgen therapy) [ 33 ]. Even though AR-positive tumors appeared more often in postmenopausal patients [ 26 , 34 , 35 ] and a higher percentage of postmenopausal women was found in the LAR subtype [ 36 ], there was no significant correlation between AR and menopausal status found [ 31 , 37 , 38 ].…”
Section: Clinical Characteristics Of Ar-positive Tnbcmentioning
confidence: 99%
“…Ki-67 was lower among the LAR subtype than in the other subtypes [ 4 , 44 , 45 ]. Similarly, AR-positive tumors were more likely to have lower Ki-67 [ 28 , 31 , 34 , 35 , 46 , 47 ] which could be due to anti-proliferative effect of AR stimulation [ 46 ], suggesting a protective role or better biological fundament with expression of AR [ 47 ]. On the contrary, AR expression was not associated with Ki-67 [ 38 ].…”
Section: Clinical Characteristics Of Ar-positive Tnbcmentioning
confidence: 99%
“…Studies show that AR can probably predict neoadjuvant treatment effects. AR expression seemed to be related to a lower pCR rate and worse outcome in TNBC [3,[17][18][19][20], but there was also controversy related to these results [21]. In HER2 positive breast cancer, AR+ positivity was associated with pCR, but in this study, only 57.3% of patients received trastuzumab [15].…”
Section: Introductionmentioning
confidence: 80%
“…AR expression has been suggested to predict the response to neoadjuvant therapy in the literature. AR-negative TNBC patients had higher pCR rates than AR-positive TNBC patients [3,[18][19][20]. In these studies, researchers often adopted 1% or 10% as the cutoff of AR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated post-NAC results based on HER2-positive or triple-negative breast cancer status [8][9][10]. Some studies have indicated that axillary pCR is associated with a biological subtype, initial clinical tumor stage, clinical nodal stage, and breast pCR [4].…”
Section: Discussionmentioning
confidence: 99%